Clinical Presentation and Conservative Management of Tympanic Membrane Perforation during Intrapartum Valsalva Maneuver - Jonathan D. Baum; Meghan I. Rattigan; Eric Scott Sills; Anthony P. H. Walsh (Case Reports in Medicine)
Background. Tympanic membrane perforation may occur when ear pressures are excessive, including valsalva maneuver associated with active labor and vaginal delivery. A pressure differential across the eardrum of about 5 psi can cause rupture; the increased intraabdominal pressure spikes repeatedly manifested by “pushing” during second-stage labor easily approach (and may exceed) this level. Material and Method. We describe a healthy 21-year old nulliparous patient admitted in active labor at 39-weeks' gestational age. Results. Blood appeared asymptomatically in the left ear canal at delivery during active, closed-glottis pushing. Otoscopic examination confirmed perforation of the left tympanic membrane. Complete resolution of the eardrum rupture was noted at postpartum check-up six weeks later. Conclusion. While the precise incidence of intrapartum tympanic membrane rupture is not known, it may be unrecognized without gross blood in the ear canal or subjective hearing loss following delivery. Only one prior published report on tympanic membrane perforation during delivery currently appears in the medical literature; this is the first English language description of the event. Since a vigorous and repetitive valsalva effort is common in normal vaginal delivery, clinicians should be aware of the potential for otic complications associated with the increased intraabdominal pressure characteristic of this technique.